To design rainwater collection system for domestic use and the economic cost analysis of the system - Lee, Kok Keong (2013)
This thesis deals with the design of the rainwater collection system for domestic use and economic cost analysis of the system. The objective of this thesis are to design rainwater collection system and analyze the economic cost of the system for a family Pekan people. Rainwater are a natural source of clean water and suitable for non-portable use and solve the water shortage problem In this study, parameters of quality of rainwater were measured such as pH, turbidity, dissolve oxygen and total suspended solid. The finite element analysis was then performed using the software of Algor Simulation. The type of analysis was static stress with linear material model analysis against the structure stand of rainwater storage tank. The annual rainfall data of 2012 will be analyzed by software of Tanki Norm Simulation to find out the reliability of the rainwater collection system. In the result, all parameters of quality of rainwater measured were acceptable by refer from the table shown by Interim National Water Quality Standards For Malaysia ( Class IIB) except the level of dissolved oxygen was quite low compare with it. From the result of Tanki Nahrim Simulation, shown that the reliability of the system was 61.23 %. In economic aspect, it found out that the rainwater cost RM 3.1 per meter cube with five year payback period of the system which is higher than RM 0.37 per meter cube of pipe water.